Renal artery variants: a comprehensive cadaveric comparative study using morphological and corrosion casting technique - Kaushik, Ram Kumar; Tripathi, Alok; Kausar, Hina; Goel, Prabhat; Raizaday, Shobhit; Dawani, Pooja (International Journal of Research in Medical Sciences, 2024)
Background: Kidneys, crucial excretory organs, receive substantial blood supply through renal arteries. Variations in their anatomy are common, warranting detailed investigation. This study aims to comprehensively examine renal artery patterns using both gross dissection and the corrosion cast method. Methods: Thirty kidney pairs from cadavers were meticulously dissected at Subharti Medical College, Meerut, U.P. India. Gross features were carefully noted, and corrosion casts were meticulously prepared. Prevalence, origin, level, division, course, and variations were exhaustively recorded to provide a thorough understanding of renal vascular anatomy. Results: Main renal arteries were found to predominantly originate from the abdominal aorta in all specimens. Interestingly, a higher prevalence of origin of right renal arteries was observed, with 47% exhibiting a higher origin than their left counterparts. Further analysis revealed prehilar division in 38.3% and hilar division in 61.6% of specimens. Notably, a segmental pattern of renal arteries was observed. Accessory renal arteries (8%) were identified, including rare occurrences of bilateral and double accessory renal arteries. Of particular significance was the observation of an accessory renal artery passing anterior to the inferior vena cava, highlighting the intricacies of renal vascular variations. Conclusions: While reaffirming the conventional understanding of renal arterial anatomy, this study emphasizes the complexity and clinical relevance of variations in renal artery morphology. Such detailed insights are invaluable for surgical and radiological practice, underlining the importance of meticulous preoperative assessment to optimize patient outcomes.